Modelling and control of a balancing robot using digital state space approach - Abdul Kadir, Herdawatie (2005)
This thesis is concerned with the problems of modelling a complete mathematical model of a balancing robot and control the system using digital state space approach to pilots the motors so as to keep the system in equilibrium. The research work is undertaken in the following development stages. In order to analyze and design the control system the dynamic of model of the system was first established in discretetime. Then the difference equation approach is used to obtain the dynamic equations of an actual experimental test-rig. The dynamic of the DC motors as well as chassis and wheels of balancing robot are incorporated in the overall dynamic model, which is in the form of continuous state-space. Two type of controllers, namely pole placement controller and LQR controller are considered in this work. The performance and reliability of both controller will be determined by performing extensive simulation using MATLAB/SIMULINK as the platform.